WiFi based device-free human activity recognition - Zhu, Zheyu (Nanyang Technological University, 2020)
Nowadays, we are in an era of information explosion. 5G technology and artificial intelligence are in the center of this technological revolution. The development of wireless devices and semiconductor devices has laid the foundation for the implementation of human behavior recognition technology. As one of the hot research topics in the Internet of Things technology, behavior recognition technology can provide convenience for many people and has strong practical application value.